ASPECTS REGARDING REQUIREMENTS OF THE RAPESEED CULTURE TOWARDS THE CLIMATIC CONDITIONS. CASE STUDY: THE IALOMIȚA COUNTY, ROMANIA - Dana Maria CONSTANTIN (OPREA); Elena GRIGORE; Elena BOGAN; Marina Aurelia ANTONESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Being a plant specific to the temperate climate with mild winters, cool and humid summers, the rapeseed is currently one of the world’s most important oil plant species, being cultivated for its oil rich seeds. The main purpose of this study is to analyze the relationship between climatic conditions and the rapeseed culture for the time interval 1990 – 2013, in the context of the climate changes. The analysis was based on the climate data collected from the meteorological stations from Urziceni, Grivița and Slobozia, on the data regarding the rape cultivated area and production in the territory of the Ialomița County. The research was carried out in the Southern Romania, in the second favorability degree area for the rapeseed culture. With the help of the analyzed data, the variability in time and space of the rapeseed culture in relation with the climatic conditions has been highlighted.